Interleukin‐13 affects the epithelial sodium channel in the intestine by coordinated modulation of STAT6 and p38 MAPK activity. (28th October 2015) - Dames, Petra; Bergann, Theresa; Fromm, Anja; Bücker, Roland; Barmeyer, Christian; Krug, Susanne M.; Fromm, Michael; Schulzke, Jörg‐Dieter
Abstract : Key points: Interleukin‐13 (IL‐13) causes intestinal epithelial barrier dysfunction, and is implicated in the pathogenesis of Th2‐driven intestinal inflammation (e.g. ulcerative colitis). However, it is unclear whether the epithelial sodium channel (ENaC) – the main limiting factor for sodium absorption in the distal colon – is also influenced by IL‐13 and if so, by what mechanism(s). We demonstrate in an intestinal cell model as well as in mouse distal colon that IL‐13 causes reduced ENaC activity. We show that IL‐13 impairs ENaC‐dependent sodium transport by activating the JAK1/2–STAT6 signalling pathway. These results improve our understanding of the mechanisms through which IL‐13 functions as a key effector cytokine in ulcerative colitis, thereby contributing to the distinct pathology of this disease. Abstract: Interleukin‐13 (IL‐13) has been strongly implicated in the pathogenesis of ulcerative colitis, possibly by disrupting epithelial integrity. In the distal colon, the epithelial sodium channel (ENaC) is an important factor in the regulation of sodium absorption, and therefore plays a critical role in minimizing intestinal sodium and water losses. In the present study, we investigated whether IL‐13 also acts as a potent modulator of epithelial sodium transport via ENaC, and the signalling components involved. The effect of IL‐13 on ENaC was examined in HT‐29/B6‐GR/MR human colon cells, as well as in mouse distal colon, by measuring amiloride‐sensitive short‐circuit current ( I SC ) in Ussing chambers. The expression levels of ENaC subunits and the cellular components that contribute to ENaC activity were analysed by qRT‐PCR and promoter gene assay. We show that IL‐13, in both the cell model and in native intestinal tissue, impaired epithelial sodium absorption via ENaC ( J Na ) as a result of decreased transcription levels of β‐ and γ‐ENaC subunits and SGK1, a post‐translational regulator of ENaC activity, due to impaired promoter activity. The reduction in J Na was prevented by inhibition of JAK1/2–STAT6 signalling. This inhibition also affected the IL‐13‐induced decrease in p38 MAPK phosphorylation. The contribution of STAT6 to IL‐13‐mediated ENaC inactivation was confirmed in a STAT6 −/− mouse model. In conclusion, these results indicate that IL‐13, the levels of which are elevated in ulcerative colitis, contributes to impaired ENaC activity via modulation of the STAT6/p38 MAPK pathways. Key points: Interleukin‐13 (IL‐13) causes intestinal epithelial barrier dysfunction, and is implicated in the pathogenesis of Th2‐driven intestinal inflammation (e.g. ulcerative colitis). However, it is unclear whether the epithelial sodium channel (ENaC) – the main limiting factor for sodium absorption in the distal colon – is also influenced by IL‐13 and if so, by what mechanism(s). We demonstrate in an intestinal cell model as well as in mouse distal colon that IL‐13 causes reduced ENaC activity. We show that IL‐13 impairs ENaC‐dependent sodium transport by activating the JAK1/2–STAT6 signalling pathway. These results improve our understanding of the mechanisms through which IL‐13 functions as a key effector cytokine in ulcerative colitis, thereby contributing to the distinct pathology of this disease.